Simulation of Multi-Angle Scanning Method for the Medical Electron Beam Transverse Profile Determination; Electron, Positron, Neutron and X–ray Scattering under External Influences - Stuchebrov S. G. Sergey Gennadevich; Batranin A. V. Andrey Viktorovich; Bulavskaya A. A. Angelina Aleksandrovna; Bushmina E. A. Elizaveta Alekseevna; Cherepennikov Yu. M. Yuriy Mihaylovich; Grigorieva (Grigorjeva) A. A. Anna Anatoljevna; Miloichikova I. A. Irina Alekseevna (2021, 2021)
Title screen